Investigating the grinding performance of unidirectional and 2.5D-C/SiCs. Issue 4 (15th February 2021) - Yang, Yuying; Qu, Shuoshuo; Gong, Yadong
Abstract: The grinding performances of unidirectional and 2.5D-C/SiCs were discussed in this paper. In particular, the effects of the grinding depth and fibre architecture on the grinding force, surface quality and grinding debris and the material removal mechanisms of C/SiCs were the main focuses of this investigation; these issues have not received much attention in previous studies. Therefore, this study attempted to analyze the grinding mechanism of C/SiCs and improve the corresponding grinding quality on the basis of discussing the grinding properties of C/SiCs with different fibre architectures. The grinding depth had a substantial influence on the grinding properties of the C/SiCs. Compared to the unidirectional C/SiCs, the 2.5D-C/SiCs sustained a higher grinding force under the same grinding parameters. Fibre pullout and fibre outcrop were the fundamental damage modes of the unidirectional C/SiCs. In contrast, interfacial debonding, matrix cracking, fibre pullout and fibre outcrop were the primary defect forms of the 2.5D-C/SiCs. The subsurface damage in the 2.5D-C/SiCs was shallower and wider than that in the unidirectional C/SiCs. In addition, there was a substantial difference between the debris from the unidirectional and 2.5D-C/SiCs. The grinding force, surface quality and grinding debris of C/SiCs with different fibre architectures can be predicted with the principles outlined in this study. Hence, this research can provide a reference for increasing the grinding performance of C/SiCs with different fibre architectures.